2022
DOI: 10.3389/fimmu.2022.954936
|View full text |Cite
|
Sign up to set email alerts
|

Role of B cells as antigen presenting cells

Abstract: B cells have been long studied for their role and function in the humoral immune system. Apart from generating antibodies and an antibody-mediated memory response against pathogens, B cells are also capable of generating cell-mediated immunity. It has been demonstrated by several groups that B cells can activate antigen-specific CD4 and CD8 T cells, and can have regulatory and cytotoxic effects. The function of B cells as professional antigen presenting cells (APCs) to activate T cells has been largely underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 229 publications
0
59
2
Order By: Relevance
“…Furthermore, the spatial orientation of CD25 + T cells are on the margins and not in the cytolytic core, suggesting that NOS2/COX2 inhibition not only changes the immune tone but also the spatial arrangement of immune mediators. Importantly, this novel spatial orientation provides an opportunity for the T cells, CD11c + DC, and B cells to cross-train each other leading to a more positive therapeutic response [ 44 ]. A study describing an in situ vaccine utilizing an IL12 agent combined with radiation demonstrated that T cell-based antigen recognition along with humoral response through cross education was important for a stable resistance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the spatial orientation of CD25 + T cells are on the margins and not in the cytolytic core, suggesting that NOS2/COX2 inhibition not only changes the immune tone but also the spatial arrangement of immune mediators. Importantly, this novel spatial orientation provides an opportunity for the T cells, CD11c + DC, and B cells to cross-train each other leading to a more positive therapeutic response [ 44 ]. A study describing an in situ vaccine utilizing an IL12 agent combined with radiation demonstrated that T cell-based antigen recognition along with humoral response through cross education was important for a stable resistance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main function of B cells during tumorigenesis is their close relationship with T cells, allowing T cells to act against tumor cells. B cells act as antigen presenting cells to T cells [134][135][136][137]. B cells are also involved in secretion of anti-tumorigenic cytokines such as IFN-γ [134][135][136][137].…”
Section: T Cellsmentioning
confidence: 99%
“…B cells act as antigen presenting cells to T cells [134][135][136][137]. B cells are also involved in secretion of anti-tumorigenic cytokines such as IFN-γ [134][135][136][137]. However, several studies also show that B cells are pro-tumorigenic in some tumors [138][139][140].…”
Section: T Cellsmentioning
confidence: 99%
“…In addition to their essential role in the humoral immune response as antibody-secreting cells and by generating antibody-mediated memory responses, B cells are also capable of acting as professional APCs and thus play an important role in immune regulation and shaping of the evolving adaptive immune response (23). B cells are able to present antigens directly or by cross-presentation with enhanced capacity for antigen presentation in response to certain stimuli, comparable to that of DCs (24). Thus, they activate naive CD8 + T cells and promote robust CD4 + and CD8 + T-cell memory responses, while also playing a dominant role in recall responses (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…B cells are able to present antigens directly or by cross-presentation with enhanced capacity for antigen presentation in response to certain stimuli, comparable to that of DCs (24). Thus, they activate naive CD8 + T cells and promote robust CD4 + and CD8 + T-cell memory responses, while also playing a dominant role in recall responses (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%